Sensitivity to 4-hydroxyestradiol and dna repair efficiency in peripheral blood lymphocytes of endometrial cancer patients - Buchynska, L.G.; Brieieva, O.V. (Experimental Oncology, 2018)
Background: The development of hormone-dependent cancers, including endometrial carcinomas, in great part may be mediated by the genotoxic effects of estrogen metabolites, among which 4-hydroxyestradiol (4OHE2) is characterized by the most prominent DNA-damaging properties. It is assumed that the individual sensitivity to the 4OHE2 may determine the predisposition to endometrial cancer (EС). Aim: To analyze the sensitivity of peripheral blood lymphocytes (PBLs) of EC patients to the 4OHE2 and to evaluate the repair efficiency of 4OHE2-induced DNA damage. Materials and Methods: The study was performed on the PBLs of 53 EC patients and 20 healthy women. The level of DNA damage was measured using the comet assay and was expressed as % tail DNA. The DNA repair efficiency (%) was evaluated by determining the ratio between the amount of repaired DNA damage and the level of 4OHE2-induced damage that appeared after incubation of PBLs with 4OHE2. Results: In PBLs of EC patients, a higher level of 4OHE2-induced DNA damage (32.0 ± 2.2% tail DNA) and lower DNA repair efficiency (34.0 ± 4.5%) was observed compared to PBLs of healthy women (22.3 ± 2.3% tail DNA and 48.8 ± 4.5%, respectively). PBLs of EC patients with deep tumor invasion of myometrium were characterized by more prominent decrease of DNA repair than those with less invasive tumor (< ½ of myometrium) (20.9 ± 7.8 and 43.7 ± 6.7%, respectively). Furthermore, lower DNA repair efficiency was detected in the PBLs of EC patients with a family history of cancer compared to this parameter in patients with sporadic tumors (20.9±7.8 and 47.1 ± 5.5%, respectively). Conclusion: The PBLs of EC patients are characterized by increased sensitivity to the genotoxic effect of 4OHE2 and reduced repair efficiency regarding 4OHE2-induced DNA damage. A lower level of DNA repair is observed in EC patients with deep tumor myometrial invasion and a family history of cancer.